1974
DOI: 10.1139/v74-092
|View full text |Cite
|
Sign up to set email alerts
|

Kinetics of Proton Transfer Reactions of Carbon Acids. IV. Primary Deuterium Isotope Effect in the Reaction of Di-(4-nitrophenyl)methane-d2 with t-Butoxide

Abstract: The primary deuterium isotope effect has been measured for the proton transfer reaction from di-(4-nitropheny1)methane to t-butoxide ion in a solvent consisting of 10% v/v toluene in 1-butanol at a series of temperatures between 20 and 45 "C. The isotopic rate ratio, kH/kD, is 7.3 at 25 "C. The activation parameters showed an enthalpy of activation difference (AHD* -AHH*) of only ra. ) kcal mol-' and an entropy isotope effect (ASD* -ASH*) of -2.4 cal mol-' deg-I. The latter indicates, according to the theory o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
3
0

Year Published

1974
1974
2001
2001

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 3 publications
1
3
0
Order By: Relevance
“…It may be seen that the rate constants and activation parameters in solvents containing 20, I I 50 and 80% v/v toluene in t-butyl alcohol form a series with the results in 10% v/v toluene-t-butyl alcohol reported earlier (3), in which the changes in these reaction characteristics are smooth. The rate constants decrease as the toluene content of the solvent is increased and are very small for solvents above 80% toluene.…”
supporting
confidence: 62%
“…It may be seen that the rate constants and activation parameters in solvents containing 20, I I 50 and 80% v/v toluene in t-butyl alcohol form a series with the results in 10% v/v toluene-t-butyl alcohol reported earlier (3), in which the changes in these reaction characteristics are smooth. The rate constants decrease as the toluene content of the solvent is increased and are very small for solvents above 80% toluene.…”
supporting
confidence: 62%
“…The proton-transfer reactions of nitroalkanes have received a great deal of attention in the past half-century. They are moderately strong C−H acids and the conjugate bases are often long-lived which coupled with strong absorbance bands in the visible region renders the kinetics readily studied by conventional techniques. The question of quantum mechanical tunneling during cleavage of the C−H bond in these compounds has been the topic of much discussion.…”
Section: Discussionmentioning
confidence: 99%
“…Numerous studies of the proton-transfer reactions of nitroalkanes with both neutral and anionic bases have been carried out over the past half-century. The reactions are conveniently studied by spectrophotometry since the stable anionic products exhibit strong absorbance bands in the visible spectral region. The very large deuterium kinetic isotope effects (≅50) reported by Caldin and Mateo 7,8 for the reaction between 4-nitrophenylnitromethane (NPNM) with tetramethylguanidine (TMG), a strong organic base with an exchangeable N−H, in toluene were quickly challenged by two groups. ,, Reinvestigations of the reaction revealed that the results reported for the D-labeled acid are unreliable due to proton/deuteron (H/D) exchange and that KIE app was lowered to about 11 when the base was changed to (Me 2 N) 2 CND.…”
mentioning
confidence: 99%
“…Many of the studies of proton tunneling in organic reactions have been concerned with proton transfer reactions of nitroalkanes, and these reactions have been treated as simple reversible second-order reactions. Since we have shown 4 that the proton transfer reactions of a representative substrate in this series, 1-nitro-1-(4-nitrophenyl)ethane, with hydroxide take place by the complex mechanism some doubt arises as to whether the previous proton tunneling discussions have dealt with KIE real or with KIE app which cannot be equated to the latter for the proton transfer steps.…”
Section: Discussionmentioning
confidence: 99%